“Validación de la población eosinofílica en bovinos de la ganadería FACIAG-UTB tratados con auto hemoterapia” - Pérez Foyain, Katriana Lorena (2023)
This experimental work was carried out at the Faculty of Agricultural Sciences, School of Veterinary Medicine and Zootechnics of the Technical University of Babahoyo. The purpose of this experimental study is to verify the effect of autohemotherapy as a stimulant of the immune system, since it is a technique that promises to increase the body's defense system by almost 100%, with an effectiveness of up to 99.9% used as a treatment for infections. and autoimmune pathologies. The treatment is little recognized by conventional or orthodox medicine, so it is of great interest to verify if autologous blood, inoculated intramuscularly, allows the increase in the number of defense cells, in this case, eosinophils. For this investigation, 12 livestock were used, the treatments were composed of: Treatment 1 (20ml dose), treatment 2 (15ml dose) and control (0ml). 12 experimental units, they were distributed under the DCA. For the evaluation and comparison of treatment measures, the Tukey test was used at 5% probability. According to the analysis of variance, there was no statistical significance. But if there was numerical significance according to the Tukey test 5% after 24 hours in T2 which started with 0.71ul and increased to 0.90ul. But nevertheless, in the 20ml dose there was a decrease from 1.00ul to 0.93ul, it should be noted that the study subjects for the 20ml dose were more complex to handle, because of it they were more stressed and this factor also influenced the results. analyte results. Yes, there was a high numerical significance in both treatments, comparing these data with those of the control. Treatment 1 has an increase of 0.17ul, and treatment 2 has an increase of 0.23ul. Consider the use of autohemotherapy in doses of 20 ml, for an alternative or adjuvant treatment of eosinopenia in semovientes, at intervals of 7 days for 5 weeks. Taking into account a good management of patients